HUBUNGAN WORK ENGAGEMENT DAN DIMENSI STAFFING PERAWAT DENGAN BUDAYA KESELAMATAN PASIEN DI RUANG RAWAT INAP RSU UKI - Rani Mutrika (2021)
Nurse performance in implementing a patient safety culture is influenced by the level of work engagement. A low patient safety culture can also occur as a result of inadequate nurse staffing. This study aims to analyze the relationship of work engagement and nurse staffing dimensions with patient safety culture at the inpatient room of RSU UKI. The method used in this study is quantitative with a cross sectional approach. Sampling techniques used are a purposive sampling of 64 respondents. The data analysis used is Chi-Square test. The results of this study showed an overview of the level of work engagement in nurses which 43 nurses (67.2%) include in low category. The staffing dimensions revealed that 33 respondents (51.6%) answered inappropriate. This study also proved that 51.6% of patient safety culture is in negative category. There is a significant relationship between work engagement (p value = 0.001) and nurse staffing dimension (p value = 0.001) with patient safety culture. Hospital management is expected to provide recognition and appreciation to nurses, as well as improve the management of nurse staffing so that work engagement in nurses can be enhaced which make the application of patient safety culture can be more optimal.